Assessing Attitudes and Participation Regarding a Pilot COVID-19 Workplace Vaccination Program in Southern Germany Considering the Occupational Health Perspective—A Mixed Methods Study - Anke Wagner; Kamil Keles; Christine Preiser; Anna T. Neunhöffer; Jana Soeder; Juliane Schwille-Kiuntke; Monika A. Rieger; Esther Rind (Vaccines, 2023)
This mixed methods study retrospectively assessed attitudes and participation of employees, occupational health personnel, and key personnel regarding the rollout of a pilot COVID-19 workplace vaccination program in five German companies in May/June 2021 in Baden-Württemberg (Southern Germany) by combining survey data and qualitative interviews. A total of 652 employees completed a standardized questionnaire and we conducted ten interviews with occupational health personnel and key personnel with other professional backgrounds organizing the pilot workplace vaccination program. Survey data were analyzed descriptively and interviews were audio recorded, transcribed verbatim, and analyzed using qualitative content analysis. Employees participated widely in COVID-19 vaccinations at their workplaces, and most employees (n = 608; 93.8%) had a full COVID-19 immunization at the time of the survey. The main advantages of the pilot COVID-19 workplace vaccination program were seen in the flexible and time-saving vaccination offer as well as the trust in and long-standing relationship with occupational health physicians. The main disadvantage of the pilot vaccination offer was increased workload for occupational health personnel, especially during the roll-out phase of the program. The pilot COVID-19 workplace vaccination program was predominantly positively assessed, and the important role of occupational health services in managing the COVID-19 pandemic was highlighted. The main criticisms of the COVID-19 workplace vaccination program related to the high organizational and administrative burden. Findings from our study can support the development of future programs for the administration of generally recommended vaccination in the workplace setting in Germany.